THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 KERITANG IN COMPREHENDING NARRATIVE TEXTS - Devi, Sri; Eliwarti, Eliwarti; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This main objective of study is to find out if there is a significant correlation between students’ motivation and their reading comprehension ability. The population of the study is 268 students of the second year students, while the sample is 35 students are by using the cluster random sampling technique. The data were collected through 25 questions reading comprehension ability test and 30 statements (questionnaires) about reading motivation. The result of the test was analysed by using Pearson Product Moment though SPSS version 23.0. From the analysis, it was found that the second year students’ of SMAN 1 Keritang were in the medium level in their reading motivation, meanwhile the students’ reading comprehension score was in the mediocre level. The correlation between both variables was in high correlation level which the coefficient of the correlation was 0.704. However, building motivation and mind-set about having a good reading motivation is essential to be recommended because it is very useful to develop students’ English skill and help them to face some tests which correlate with students’ reading comprehension ability.Key Words: Correlation, Reading Motivation, Reading Comprehension